Human error dan kelemahan kontrol internal sebagai pemicu risiko operasional: Studi kasus gangguan sistem Bank Syariah Indonesia - Romadhoni, Ahmad Rizqi (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of human error and weak internal controls as triggers of operational risk in Islamic banking through a case study of the Bank Syariah Indonesia (BSI) system disruption in May 2023. The research employed a descriptive qualitative approach based on a conceptual case study using literature review, incident chronology analysis, and linkage of findings with operational risk and internal control theories. The results indicate that operational risk is not solely caused by external factors such as cyberattacks, but is also significantly influenced by internal factors. The suspected use of outdated systems, weak access controls, low employee cybersecurity awareness, and slow monitoring and incident response were identified as indicators of ineffective internal control systems. The combination of these factors amplified the disruption, causing failures in ATM services, mobile banking, and branch transactions nationwide. In the context of Islamic banking, operational incidents also reduce customer trust, which is the main foundation of the industry. Therefore, Islamic banks need to strengthen COSO-based internal controls, enhance human resource capacity through cybersecurity training, conduct regular information technology audits, and establish effective disaster recovery plans and business continuity plans to mitigate operational risk in the digital era.